Problems and trends of regional tourism development in Latvia - Jelena Lukjanova (Економіка, Eкологія, Cоціум, 2019)
Introduction. Tourism industry is one of the most promising and rapidly developing sectors of the global economy. In modern conditions of increased competition in the global market of tourist services, the problem of increasing the competitiveness of the tourism industry in Latvia is becoming more urgent, and studying the issue of the competitiveness of regional tourist markets is particularly relevant. The level of competitiveness of a particular region determines its success in relation to other regions of the state and the world, indicates the presence of existing problems and helps to find solutions to them.